(untitled) (Communications in Computational Physics, 2018)
Superconvergence for the lowest-order edge finite elements on strongly regular triangulation is studied. By the averaging technique, superconvergence of order O(h2) is established at the midpoint of the interior edge for both the finite element solution and the curl of the finite element solution. Numerical results justifying our theoretical analysis are presented.